2018
DOI: 10.1136/bmjopen-2018-022266
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of exercise referral schemes enhanced by self-management strategies to battle sedentary behaviour in older adults: protocol for an economic evaluation alongside the SITLESS three-armed pragmatic randomised controlled trial

Abstract: IntroductionPromoting physical activity (PA) and reducing sedentary behaviour (SB) may exert beneficial effects on the older adult population, improving behavioural, functional, health and psychosocial outcomes in addition to reducing health, social care and personal costs. This paper describes the planned economic evaluation of SITLESS, a multicountry three-armed pragmatic randomised controlled trial (RCT) which aims to assess the short-term and long-term effectiveness and cost-effectiveness of a complex inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Furthermore, ongoing research and developments could not be included which could be important in such a dynamically moving area. For example, we found information about ongoing economic evaluations [41,42,114] with the identified instruments where results expected to be published soon, additional capability instruments might have been used in unpublished economic evaluations, or some are currently under development. There is a potential need to update this literature review in the future to gather information from this rapidly growing body of literature about the potential development of additional capability measures, the further validation of existing ones, the empirical use of capability measures in economic evaluations, and the lessons learned from these applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ongoing research and developments could not be included which could be important in such a dynamically moving area. For example, we found information about ongoing economic evaluations [41,42,114] with the identified instruments where results expected to be published soon, additional capability instruments might have been used in unpublished economic evaluations, or some are currently under development. There is a potential need to update this literature review in the future to gather information from this rapidly growing body of literature about the potential development of additional capability measures, the further validation of existing ones, the empirical use of capability measures in economic evaluations, and the lessons learned from these applications.…”
Section: Discussionmentioning
confidence: 99%
“…The number of economic evaluations reporting the use of a capability instrument has increased in recent years and further increases can be expected given that this search identified a number of recent study protocols (e.g. [41,42,114]). Four further studies were identified that specifically addressed the issues and discussed considerations when incorporating the capability approach into health-related economic evaluations.…”
Section: Applied Economic Evaluations and Potential Methods To Incorpmentioning
confidence: 99%
“…Patient engagement and patient activation are major focuses of health policy efforts [ 4 6 ]. A large proportion of chronic diseases, for example hypertension, ischemic heart disease and diabetes, requires the patient to take active actions daily, called self-care [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of an ongoing multicountry, multicentre RCT examining the cost-effectiveness of enhanced ERSs plus self-management strategies compared with ERS alone among inactive patients. 73 This chapter addresses the gaps in the literature by estimating the cost-effectiveness of e-coachER compared with ERSs alone, in adults with range of chronic conditions. The analysis uses a 1-year time horizon (from baseline to 12 months post randomisation) and is conducted from the viewpoint of the NHS, Personal Social Services and patients.…”
Section: Chapter 5 Economic Evaluation Introductionmentioning
confidence: 99%